Clinicopathological Study of Gastroduodenal Biopsies and Correlate with Endoscopic Findings in Northeast India- One- Year Cross-sectional Study in a Tertiary Care Centre - Sarma, Usha; Kalita, Upasana (Asian Pacific Journal of Cancer Biology, 2024)
Background: The gastrointestinal tract (GIT) is a hollow muscular tube extending from the oral cavity to the anus. Acid peptic disease is among the most common disorders affecting this region globally, caused by an imbalance between acid secretion and gastric mucosal defenses. Endoscopy has enhanced the accuracy and early histologic diagnosis of mucosal lesions. This cross-sectional study examines 100 gastroduodenal biopsies over a one-year period. Methods: The study categorized histopathological findings from gastro-duodenal biopsies collected via endoscopy and analyzed their correlation with endoscopic results. Results: Gastroduodenal lesions were more prevalent in males, particularly in the fifth decade of life. Endoscopic findings included 12 normal cases, 31 ulcers, 15 erosions, 4 polyps, and 38 malignancies. Among the 38 malignancies, 10 were premalignant, 23 were diagnosed as gastric carcinoma, and 4 as duodenal carcinoma, demonstrating a strong correlation between endoscopic and histopathological findings. Conclusion: Endoscopic gastroduodenal biopsies are instrumental in diagnosing both benign and malignant lesions across various age groups and sites. The combination of endoscopy and histopathological analysis provides a powerful diagnostic tool for better patient management.